Evaluating factors impacting early career physician-scientists’ decisions to continue research careers in the United States of America - Kassem Farhat; Aleksandar Obradovic; Aisha Siebert; Han Naung Tun; Evan K. Noch; Jennifer M. Kwan (BMC Medical Education)
Abstract Background Bridging the gap between laboratory discoveries and patient care relies heavily on the physician-scientist workforce, which has historically served as a cornerstone in advancing biomedical sciences. However, the past decade has witnessed a remarkable decline in the number of emerging physician-scientists, raising concerns about the future of this vital community. This study aimed to evaluate the current state of early career physician-scientists on a national scale and explore challenges that hinder its growth, thereby limiting potential scientific innovation and progress. Methods A survey was conducted in the United States and distributed to 110 nationally representative institutions using an online platform (SurveyMonkey), targeting physician-scientists at their late stage of clinical training (residents/fellows) and graduates of training programs within the past 10 years. 265 submitted results but after filtering for incomplete responses, a total of 230 survey results were used in the analysis. The survey evaluated scientific career trajectories, challenges encountered, and top priorities. Statistical analyses, including Chi-square and Fisher’s exact tests, were used to compare differences between groups. Results A total of 230 physician-scientists completed the survey. The respondents were predominantly assistant professors (46%), while 27% were still enrolled in career training programs. Nearly half of the participants reported considering leaving their research career within the next two years. The primary reasons cited for this included burnout and unhappiness (35%), stress (35%), and lack of funding (30%). The most frequently reported career challenges were achieving a balance between clinical and educational responsibilities (63%) and maintaining work-life balance (53%), followed by insufficient research funding (41%). Additionally, participants underscored key factors they prioritize when seeking employment, including hybrid research-clinical opportunities (67%), work-life balance (52%), and financial security (26%). Conclusion This national survey provides an overview of the current state of early-career physician-scientists. It examines the factors contributing to the inclination to leave the scientific track and identifies the primary career challenges faced by this vulnerable community. Furthermore, it highlights key priorities of physician-scientists and gaps that require attention, offering valuable insights into strategies for retaining and supporting this critical workforce.